The kitchen house [compact disc, unabridged] - Grissom, Kathleen (Blackstone Audio Inc., 2010)
"When a white servant girl violates the order of plantation society, she unleashes a tragedy that exposes the worst and best in the people she has come to call her family. Orphaned while onboard a ship from Ireland to America, seven-year-old Lavinia arrives on the steps of a tobacco plantation where she is to live and work with the slaves of the kitchen house. Under the care of Belle, the master's illegitimate daughter, Lavinia becomes deeply bonded to her adopted family, though she is set apart from them by her white skin. Eventually, Lavinia is accepted into the world of the big house, where the master is absent and the mistress battles opium addiction. Lavinia finds herself perilously straddling two very different worlds. When she is forced to make a choice, loyalties are brought into question, dangerous truths are laid bare, and lives are put at risk"--Publisher's description.